2020
DOI: 10.1016/j.jss.2019.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Phosphatidylserine Blockade in Hemorrhagic Shock

Abstract: Introduction: Phosphatidylserine (PS) is a key cell membrane phospholipid normally maintained on the inner cell surface, but externalizes to the outer surface in response to cellular stress. We hypothesized that PS exposure mediates organ dysfunction in hemorrhagic shock.Our aims were to evaluate PS blockade on: 1) pulmonary, 2) renal, and 3) gut function, as well as 4) serum lysophosphatidic acid (LPA), an inflammatory mediator generated by PS externalization, as a possible mechanism mediating organ dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Development of such imaging modalities could be used not only to explore the contribution of the endothelium to thrombosis in severe infections, but other conditions where endothelial dysfunction may contribute to pathophysiology, such as acute kidney injury or systemic hypotension. Studies with an engineered annexin V dimer, for example, suggest its potential for improving health, even in the absence of proof of high levels of circulating PS in targeted disease states [ 61 , 62 , 63 ].…”
Section: How Could Recognition Of Ps's Role In Pathophysiology Improvmentioning
confidence: 99%
“…Development of such imaging modalities could be used not only to explore the contribution of the endothelium to thrombosis in severe infections, but other conditions where endothelial dysfunction may contribute to pathophysiology, such as acute kidney injury or systemic hypotension. Studies with an engineered annexin V dimer, for example, suggest its potential for improving health, even in the absence of proof of high levels of circulating PS in targeted disease states [ 61 , 62 , 63 ].…”
Section: How Could Recognition Of Ps's Role In Pathophysiology Improvmentioning
confidence: 99%
“…Moreover, diannexin was shown to protect against renal, lung, pancreatic, and hepatic ischemia reperfusion injury (IRI) in mice [47][48][49][50] and might thus reduce rejection responses of organ transplants. It also reduced infarct size within hours following severe myocardial ischemia in rabbits [51] by suppression of inflammatory responses and was helpful in critical conditions such as sepsis and hemorrhagic shock [30,31]. Besides diannexin, the blood half-life of anxA5 has been extended to about 5 h in mice by chemically coupling multiple PEG chains via the amine groups of anxA5 [52].…”
Section: Discussionmentioning
confidence: 99%
“…In myocardial ischemia–reperfusion injury, anxA5 was shown to suppress the inflammatory response and reduce infarction size [ 29 ]. A dimeric anxA5, administered after the onset of hemorrhagic shock or sepsis, was able to protect the lungs, kidneys, and gut from massive dysfunction [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of physiological processes such as cell activation and apoptosis, PS is externalized to the outer surface of cells, thus driving various pathological processes such as infectious diseases and cancer. 42,43 Studies have shown that low levels of PS are observed in both follicular fluid and endometrial tissue in patients with endometriosis, which may be related to a decrease in apoptotic cells in the endometrium of patients. 44,45 PA(37:4) can affect cell growth, proliferation, migration and invasion by involvement in cell signaling.…”
Section: Evaluation Of the Diagnostic Performance Of The Biomarkersmentioning
confidence: 99%